Relationships between altitude and depressive symptoms among middle-aged and older adults in China: a longitudinal study from the China health and retirement longitudinal study - Ma, Qing; Jiang, Wei; Zhao, Qiuyan; Xia, Xin; Fang, Ronghua (Frontiers in Psychiatry, 2024)
Background: Previous studies have consistently documented positive associations between depressive symptoms and altitude; however, a longitudinal study of these relationships among middle-aged and older adult community populations in China has not been previously reported.We screened 17,705 subjects who met the inclusion criteria from the China Health and Retirement Longitudinal Study database 2011. The altitude is the altitude at which the participants lived in our study area. We estimated the prospective associations between altitude and depressive symptoms among middle-aged and older adults. The 10-item Center for Epidemiological Studies Depression Scale short form was used to measure depressive symptoms. A total of 6,594 participants without depressive symptoms were recruited from the same cohort in 2011 and were followed up in 2018. Multivariate logistic regression was used to assess the associations between altitude and depressive symptoms among middle-aged and older adults.The prevalence of depressive symptoms was 27.3% in our study. The prevalence of depressive symptoms increased with increasing altitude, and the prevalence of depressive symptoms in women was greater than that in men.Multivariate logistic regression adjusted for all other relevant variables showed that sex, altitude, education level, professional status and marital status were associated with depressive symptoms.This finding provides evidence of the relationship between altitude and depressive symptoms among middle-aged and older adult community populations in China and shows that depressive symptoms are significantly positively correlated with altitude and other factors, including sex, education level, professional status, and marital status.